2015
DOI: 10.1016/j.chembiol.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Detergent, Temperature, and Lipid on the Oligomeric State of MscL Constructs: Insights from Mass Spectrometry

Abstract: The mechanosensitive channel of large conductance (MscL) acts as an emergency release valve for osmotic shock of bacteria preventing cell lysis. The large pore size, essential for function, requires the formation of oligomers with tetramers, pentamers, or hexamers observed depending on the species and experimental approach. We applied non-denaturing (native) mass spectrometry to five different homologs of MscL to determine the oligomeric state under more than 50 different experimental conditions elucidating li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 49 publications
7
75
1
Order By: Relevance
“…In addition to phospholipids, a second unexpected series of peaks with adduct masses of ϳ3.3 kDa was observed. We attribute these adducts to lipopolysaccharides (LPS), in agreement with a recently published study where it was shown that MscL, an inner membrane protein, has the tendency to bind to outer membrane lipids or lipopolysaccharides (21). Given that LPS are larger than phospholipids or CARD, consisting of several hydrocarbon chains, their size implies hydrophobic binding to the surface of the protein.…”
Section: Mass Spectrometry Of Mcjd Revealssupporting
confidence: 74%
“…In addition to phospholipids, a second unexpected series of peaks with adduct masses of ϳ3.3 kDa was observed. We attribute these adducts to lipopolysaccharides (LPS), in agreement with a recently published study where it was shown that MscL, an inner membrane protein, has the tendency to bind to outer membrane lipids or lipopolysaccharides (21). Given that LPS are larger than phospholipids or CARD, consisting of several hydrocarbon chains, their size implies hydrophobic binding to the surface of the protein.…”
Section: Mass Spectrometry Of Mcjd Revealssupporting
confidence: 74%
“…The closed crystal structure of pentameric M. tuberculosis MscL [4] has been known for several years. Native mass spectrometry of MscL suggested the in vitro oligomerisation state (pentamer vs tetramer) is influenced by temperature, detergent and amino acid variability as well as by the precise construct used [18]. Protein stability has been shown to be influenced by the presence of particular lipids [19].…”
Section: Bacterial Mechanosensors Mscs and Mscl: Open And Shut Storiesmentioning
confidence: 99%
“…It is becoming more and more apparent (from EM, X-ray crystallography and MS studies [22,96,[98][99][100]) that there is an intimate relationship between MPs and the surrounding lipid environment, whereby the binding of key lipids is important for maintaining MP structure and function [98]. Detergents are a poor mimic of the native bilayer, may not permit the retention of MP-lipid interactions [101], and in many cases disturb the correct, functional oligomeric state of MP assemblies [90,95,96].…”
Section: Detergent-free Methods For Native Msmentioning
confidence: 99%
“…Detergents are a poor mimic of the native bilayer, may not permit the retention of MP-lipid interactions [101], and in many cases disturb the correct, functional oligomeric state of MP assemblies [90,95,96]. Consequently, a variety of detergent-free methods have been developed to solubilize MPs for biophysical analyses, namely nanodiscs [102], bicelles [103], liposomes [104], styrene maleic acid lipid particles (SMALPs) (also called lipodisq) [93] and amphipols (Fig.…”
Section: Detergent-free Methods For Native Msmentioning
confidence: 99%
See 1 more Smart Citation